Simultaneous CO2 absorption, mineralisation and carbonate crystallisation promoted by amines in a single process. Issue 51 (September 2021) - Ji, Long; Zhang, Long; Zheng, Xuan; Feng, Liang; He, Qingyao; Wei, Yibin; Yan, Shuiping
Graphical abstract: Highlights: Process integration of CO2 carbonation with precise controlled CaCO3 products. Amine facilitated Ca(OH)2 dissolution. PZ provided the highest CaCO3 purity, CO2 removal efficiency, and diversity of product size/shape, and nearly zero amine loss in products. Abstract: Single-step CO2 absorption and mineralisation not only fulfills the advantage of rapid CO2 absorption of amines but also allows the in-situ CO2 mineralisation and amine regeneration. However, the technical feasibility of this process with various amine types has not been fully investigated. The mechanisms of amine promoted carbonation in this process was also unclear. In this study, the CO2 absorption, mineralisation and carbonate crystallisation at different monoethanolamine (MEA) concentrations, calcium hydroxide (Ca(OH)2 ) concentrations, temperatures, and amine types were systematically investigated. The dissolution experiments of Ca(OH)2 in MEA solutions with various concentrations and protonated ratio were carried out to explore the mechanisms of amine promoted carbonation. To further demonstrate the practical feasibility of this process for CO2 removal from realistic gas streams, the CO2 removal efficiencies from artificial biogas and the amine loss in CaCO3 products were determined. We found that the increased MEA and Ca(OH)2 concentrations can not only contribute to CO2 absorption but also affect the crystal sizes and shapes of calcium carbonate (CaCO3 ) products, which provided the possibility for precise product control. MEA could enhance the dissolution of Ca(OH)2 and calcium leaching, leading to the improved carbonation. Under the optimized conditions (0.5 M amine, 1.0 M Ca(OH)2, and 55 °C temperature), piperazine (PZ) was the most suggested promotor as it provided the highest CaCO3 purity (87 %), CO2 removal efficiency (98 %), diverse crystal sizes and shapes, and nearly zero amine loss in CaCO3 products.